2020
DOI: 10.1007/s00018-020-03517-8
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma-associated fibroblasts impair CD8+ T cell function and modify expression of immune checkpoint regulators via increased arginase activity

Abstract: This study shows that melanoma-associated fibroblasts (MAFs) suppress cytotoxic T lymphocyte (CTL) activity and reveals a pivotal role played by arginase in this phenomenon. MAFs and normal dermal fibroblasts (DFs) were isolated from surgically resected melanomas and identified as Melan-A-/gp100-/FAP+ cells. CTLs of healthy blood donors were activated in the presence of MAF-and DF-conditioned media (CM). Markers of successful CTL activation, cytotoxic degranulation, killing activity and immune checkpoint regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 59 publications
(71 reference statements)
1
54
0
2
Order By: Relevance
“…Ersek et al were able to determine that melanoma-associated fibroblasts (MAFs), or CAFs in melanoma cancer tissues identified by their FAP expression, impaired cytotoxic T lymphocyte function [ 42 ]. Their findings demonstrated that in the presence of MAF-conditioned media, cytotoxic T lymphocytes displayed dysregulated ERK1/2 and NF-κB signaling, impeded CD69 and granzyme B production, impaired killing activity, and upregulated expression of negative immune checkpoint receptors T cell immunoreceptor with Ig and ITIM domains (TIGIT) and B- and T- lymphocyte attenuator (BTLA).…”
Section: Effects Of Cafs On Immune Cells In the Tumor Microenvironmentioning
confidence: 99%
“…Ersek et al were able to determine that melanoma-associated fibroblasts (MAFs), or CAFs in melanoma cancer tissues identified by their FAP expression, impaired cytotoxic T lymphocyte function [ 42 ]. Their findings demonstrated that in the presence of MAF-conditioned media, cytotoxic T lymphocytes displayed dysregulated ERK1/2 and NF-κB signaling, impeded CD69 and granzyme B production, impaired killing activity, and upregulated expression of negative immune checkpoint receptors T cell immunoreceptor with Ig and ITIM domains (TIGIT) and B- and T- lymphocyte attenuator (BTLA).…”
Section: Effects Of Cafs On Immune Cells In the Tumor Microenvironmentioning
confidence: 99%
“…Moreover, ECM remodeling by CAFs may impede trafficking of T cells leading to more restrained tumor immunity [ 45 ]. CAFs also suppress the function of T cells and inhibit their tumor cell killing capacity by limiting T cell infiltration into the tumor and inhibition of the T cells cytotoxic activity within the TME [ 46 , 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…After antigen presentation, CAFs directly interact with activated CD8+ T cells, thus promoting T cell dysfunction and death via PD-L2 and FASL engagement [ 186 ]. Furthermore, Érsek et al demonstrated that MAFs can hamper cytotoxic T cell-mediated killing by altering ERK1/2 and NF-κB signalling pathways, impeding the expression of the early T cell activation marker CD69 and granzyme B production, and enhancing the expression of two potent negative regulators of T cell activity, T cell immunoreceptor with Ig and ITIM domains (TIGIT) and B and T lymphocyte attenuator (BTLA) [ 187 ]. As previously discussed, the reduction of glucose availability in the melanoma microenvironment is associated with the generation of a glucose-deficient and immunosuppressive milieu, where different cells compete for glucose uptake [ 3 ].…”
Section: Mafs As a Key Driver Of Melanoma Growth And Progressionmentioning
confidence: 99%
“…The increase of L-Arginine metabolism observed in melanoma and other human cancers, is involved in tumor progression, associated with neovascolarization and immune suppression induction [ 189 ]. In particular, L-arginine depletion in the TME induces T cell suppression facilitating the melanoma escape from immunosurveillance [ 3 , 187 ]. Of note, Ersek et al showed an increased L-arginase activity in MAFs.…”
Section: Mafs As a Key Driver Of Melanoma Growth And Progressionmentioning
confidence: 99%